THE EFFECT OF BILLBOARD CONTENT ON THE ELECTABILITY OF FEMALE MAYORAL CANDIDATES IN KENDARI CITY IN 2024 - Sirajuddin, Sirajuddin; Anggraini, Dewi; Atnan, Nur; Harnia, Sitti (Universitas Padjadjaran, 2026)
This study aims to analyze the effect of billboard content on the electability of female mayoral candidates in the 2024 Kendari City Regional Head Elections (Pilkada). The main issue underlying this study is the fact that every Pilkada in Kendari City always features female candidates, but they repeatedly experience defeat despite conducting political campaigns through various outdoor media, including billboards. The method used is a descriptive quantitative approach with simple random sampling technique and a total of 123 respondents. The independent variable in this study is billboard content, while the dependent variable is candidate electability. Data were collected through a five-point Likert scale questionnaire and analyzed using simple linear regression with the help of SPSS version 26. The results showed that billboard content had a positive and significant effect on the electability of female candidates (Hₐ accepted and H₀ rejected), with a value of R = 0.471, R² = 0.222, and significance p = 0.000. This means that 22.2% of the variation in candidate electability is explained by the quality of billboard content, especially in terms of visual aspects, social messages, and gender issues. These findings prove that billboards are still an effective campaign medium in enhancing the image and electability of female candidates at the local level. This finding confirms that billboards still have a strategic function in local political communication because they are able to build image, assert the political identity of candidates, and convey social and gender issues that are relevant to the political goals of female candidates. This study implies that optimizing billboard content can contribute to increasing the political competitiveness of women in electoral contests at the regional level.